Synthesis, Characterization and Analytical Applications of Novel Electroactive Sensor based on Titanium(IV) Tungstovanadate for Determination of Cadmium - Sharma, Harish Kumar; Parmar, Anju; Dogra, Pernita (Asian Journal of Chemistry, 2017)
The novel exchanger titanium(IV) tungstovanadate has been prepared by sol-gel method. The characterization of sensor has been done with FTIR, SEM, EDS and X-ray diffraction studies. Membranes containing different composition of electroactive material and epoxy resin as binder were prepared. The membrane with 60 % electroactive material and 40 % epoxy binder gives the best response. Potentiometric result shows that the sensor can be used in the concentration range of 10-7 to 10-1 M Cd(II) ions with a near Nernstian slope of 21 mV/decade. The electrode shows a fast response time of < 10 sec. The working pH range of the electrode is 2.62 to 8.66 and it behaves well in the partially non aqueous medium upto 30 % concentration of ethanol, methanol and acetone. Fixed interference method was used for determining the selectivity coefficient with respect to different metal ions like Pb2+, Cr3+, La2+, Co2+, Hg2+, As3+, Cu2+, Ni2+, Mn2+, Sm3+ etc. and effect of internal solution was also studied. The developed sensor can be used as an indicator electrode in the potentiometric titration of Cd(II) against EDTA and oxalic acid.